Visual Mismatch Negativity: A Mini-Review of Non-pathological Studies With Special Populations and Stimuli - Czigler, István; Kojouharova, Petia (Frontiers in Human Neuroscience, 2022)
In this mini review we summarize the results of 12 visual mismatch negativity (vMMN) studies that attempted to use this component as a tool for investigating differences between non-clinical samples of participants as well as the possibility of automatic discrimination in the case of specific categories of visual stimuli. These studies investigated the effects of gender, long-term differences between groups of participants (fitness, experience in different sports, and internet addiction), and short-term states (mental fatigue and hypoxia) as well as the vMMN effect elicited by artworks as a special stimulus category.